Role of the VCA domain of WASP in filopodia formation. - Gunaseelan Narayanan. (2009)
Wiskott-Aldrich syndrome protein (WASP) is implicated in Wiskott-Aldrich Syndrome (WAS), which is a genetic disorder. The Verprolin Cofilin Acidic (VCA) domain of WASP can activate the Actin-related protein2/3 (Arp2/3) complex but whether this property is associated with the possible ability of WASP to induce filopodia is not clearly understood. Hence, to analyze the effects of the VCA domain of WASP on filopodia formation, the different sub-domains of the VCA domain were deleted and their ability to induce filopodia in Neural-WASP (N-WASP)-/- fibroblasts was analyzed. Filopodia could still be induced after deletion of the VCA domain, suggesting that the VCA domain is not essential for filopodia formation. Further analysis indicates that the V sub-domain may act as a sensor to inhibit filopodia formation. In addition, the role of WASP-interacting protein (WIP) on WASP activity was investigated by studying the ability of WASP to induce filopodia in the presence and absence of WIP. WIP had no significant effect on filopodia formation, suggesting that WIP binding may play other roles in WASP activity. Through these findings, the complete functions of WASP and its binding partners can be better understood in the aim of finding drugs to treat WAS.